RANCANG BANGUN SISTEM INFORMASI PENILAIAN KINERJA PEGAWAI MENGGUNAKAN METODE PSYCOLOGICAL APPRAISAL (StudiKasus :Kantor Wilayah Kementerian Agama DKI Jakarta) - Yunita Adhawiyah; Nia Kumaladewi; Meinarini Catur Utami (STUDIA INFORMATIKA: JURNAL SISTEM INFORMASI, 2017)
Regional Office of the Ministry of Religious Affairs of DKI Jakarta is the Ministry in the government of Indonesia in charge of religious affairs. To realize the implementation of government and development duties required Civil Servants professional, responsible, honest, and fair through coaching conducted under the system of work performance. However, the appraiser officials have difficulty in making a decision to be able to find the right person for the right position. From those problems, the existing assessment, there is no personality assessment method that can be used as a tool in decision making. The system design is made by Rapid Application Development (RAD) method, and with UML (Unified Modeling Language) system modeling. The data analysis model is used to analyze and assess which employees can be assigned tasks or authority in accordance with their personality using the Psycological Appraisal Method and focused on the MBTI assessment indicator. The results of this study is an employee performance appraisal information system that can perform, process and see the results of personality tests quickly and in accordance with the provisions set previously also in accordance with the method of psychology.